Consumption taxation to finance pension payments - Kilian Ruppert; Matthias Schön; Nikolai Stähler (Deutsche Bundesbank, 2021)
This paper assesses how a permanent shift from financing a public pay-as-you-go pension by direct (labour income) taxation towards financing it by indirect(consumption) taxation affects the economy and welfare. To this end, we use anoverlapping-generations-augmented two-region general equilibrium framework withsearch frictions on the labour market. The analysed tax reform partially shifts thetax burden from domestic to foreign producers and lowers marginal costs of domes-tic production and generates positive domestic macroeconomic effects. In addition,the partial postponement of a household's tax burden to retirement leads to highersavings and increases domestic assets. However, for some time after implementationof the tax reform, the policy-induced increase in consumption costs makes retireesand households close to retirement worse off. Moreover, the increase in domesticnet foreign assets implies that consumption of foreign households eventually falls,which stands in contrast to what is commonly found in models without an endoge-nous savings motive.
Keywords: E24; E62; H21; H55; J26; 330; Fiscal devaluation; OLG models; Pension system; Optimal taxation